2021
DOI: 10.3390/ijerph18147309
|View full text |Cite
|
Sign up to set email alerts
|

Cigar-Smoking-Cessation Interest and Experience among Black Young Adults: A Semi-Structured In-Depth Interview Investigation

Abstract: Although Black/African American populations have high cigar-smoking prevalence, little is known about cigar-smoking cessation among this group. This study explored the perceptions and experiences of cigar-smoking cessation and assistance received from healthcare providers among forty Black young-adult cigar smokers (ages 21–29). Semi-structured in-depth phone interviews were transcribed and coded. Qualitative data were analyzed by using thematic analysis. Participants mostly smoked cigarillos, large cigars, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(61 reference statements)
2
8
0
Order By: Relevance
“…We found that perceived addiction to cigar products may be the lowest among blunt smokers, which builds on previous research that found that blunt smokers have low perceptions of harm from cigar smoking and little interest in quitting smoking [ 29 ]. Together, our findings indicate a lack of knowledge among our participants that smoking blunts may result in harm and have risks associated with smoking combustible tobacco products as well as cannabis [ 18 , 42 ].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…We found that perceived addiction to cigar products may be the lowest among blunt smokers, which builds on previous research that found that blunt smokers have low perceptions of harm from cigar smoking and little interest in quitting smoking [ 29 ]. Together, our findings indicate a lack of knowledge among our participants that smoking blunts may result in harm and have risks associated with smoking combustible tobacco products as well as cannabis [ 18 , 42 ].…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, our finding that more than half of predominant cigarillo smokers identified themselves as addicted to cigar products is consistent with a recent study exploring self-perceptions of addiction among adolescent and young adult cigarillo smokers [ 41 ]. Black young adults who predominantly smoked cigarillos were also more likely to report interests and motivations in quitting cigar products than smokers of other cigar and blunt products [ 29 ]. Therefore, interventions for treating cigar addiction and cessation can first target cigarillo smokers who may already be aware of their addiction to the products and are interested in quitting smoking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations